Perlawanan Terhadap Kekerasan Simbolik dalam Drama Undercover High School (Analisis Semiotika Roland Barthes) - Rahma Nastiti Damayanti; Yudha Wirawanda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The Korean drama Undercover High School was quite popular in 2025, which raised the theme of social inequality in the school education environment. This drama packaged the existence of social inequality in the lower class so that resistance aided by the middle class against symbolic violence from the upper class made the drama interesting to study. The purpose of this study was to determine how social inequality causes symbolic violence so that there is a difference between rich and poor students in the drama Undercover High School. The method used was qualitative analysis. The data analysis technique in the research of the drama Undercover High School used semiotics from Roland Barthes with primary data observing and watching the conversations of the drama subjects. Then the secondary data was obtained from journal literature, books and websites related to this research topic. In this study, researchers used data validity through triangulation and involved various sources for data accuracy. The results of the study found that social inequality resulted in symbolic violence from Pierre Bourdieu, which caused resistance from the lower class that occurred at the elite school Byeongmun High School.